2021
DOI: 10.5194/gmd-2021-242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determining the sensitive parameters of WRF model for the prediction of tropical cyclones in the Bay of Bengal using Global Sensitivity Analysis and Machine Learning

Abstract: Abstract. The present study focuses on identifying the parameters from the Weather Research and Forecasting (WRF) model that strongly influence the prediction of tropical cyclones over the Bay of Bengal (BoB) region. Three global sensitivity analysis (SA) methods, namely the Morris One-at-A-Time (MOAT), Multivariate Adaptive Regression Splines (MARS), and surrogate-based Sobol' are employed to identify the most sensitive parameters out of 24 tunable parameters corresponding to seven parameterization schemes of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It will therefore be important to re-examine these and other cyclone cases using revised RAL physics definitions. For example, Baki et al (2021) found simulation of TCs in Bay of…”
Section: Impact Of Coupling On Wind Speedmentioning
confidence: 99%
“…It will therefore be important to re-examine these and other cyclone cases using revised RAL physics definitions. For example, Baki et al (2021) found simulation of TCs in Bay of…”
Section: Impact Of Coupling On Wind Speedmentioning
confidence: 99%
“…The WRF model version 3.9.1 (Skamarock et al 2008) The WRF model represents the unresolved physical processes through seven parameterization schemes: surface layer physics, land surface physics, shortwave radiation, longwave radiation, planetary boundary layer physics, microphysics, and cumulus physics. The parameterization schemes used in the present work are selected based on the studies of Baki et al (2021b), which are: MM5 similarity scheme (Beljaars 1995) for surface layer physics, Unified Noah land surface model (Mukul Tewari et al 2004) for land surface physics, Dudhia shortwave scheme (Dudhia 1989) for shortwave radiation, rapid radiative transfer model (Mlawer et al 1997) for longwave radiation, WRF Single-Moment 6-class (WSM6) scheme (Hong and Lim 2006) for microphysics, Kain-Fritsch (Kain 2004) for cumulus physics, and Yonsei University Scheme (YSU) for planetary boundary layer physics. The parameterization schemes contain a vast number of tunable parameters, and calibrating all of them is an impossible task.…”
Section: Design Of Numerical Experiments a Wrf Model Configuration An...mentioning
confidence: 99%
“…The parameterization schemes contain a vast number of tunable parameters, and calibrating all of them is an impossible task. Baki et al (2021b) conducted a sensitivity study of 24 parameters from the same physics schemes for tropical cyclones over the Bay of Bengal and reported that a total of eight parameters were found to be most sensitive. Thus, these parameters are selected for calibration to improve the prediction of tropical cyclones over the BoB.…”
Section: Design Of Numerical Experiments a Wrf Model Configuration An...mentioning
confidence: 99%
See 2 more Smart Citations